Bio-Medical Waste Handling Practices in Urban Health Centers of Surat Municipal Corporation - Naik, Ashish; Modi, Bhautik; Bansal , RK (National Journal of Community Medicine, 2012)
Background: Biomedical waste consists of solids, liquids, sharps, and laboratory waste that are potentially infectious or dangerous and are considered biomedical waste. It must be properly managed and safely disposed. Methodology: Cross-sectional study design, consisting of participant observation and interviews, among 20 health centres of Surat Municipal Corporation area. Results: Our study shows number of bags having inappropriate content was maximum in red bags (50.0%). Among the medical officers and nurse, knowledge regarding proper bag for collection of cotton gauze pieces and empty box is better than all other article. Conclusion: Healthcare waste management should be supported through appropriate education, training and the commitment of the healthcare staff, management and healthcare managers.